2014
DOI: 10.1177/0883073813516192
|View full text |Cite
|
Sign up to set email alerts
|

The Ketogenic Diet as Broad-Spectrum Treatment for Super-Refractory Pediatric Status Epilepticus

Abstract: Refractory status epilepticus carries significant morbidity and mortality. Recent reports have promoted the use of the ketogenic diet as an effective treatment for refractory status epilepticus. We describe our recent experience with instituting the ketogenic diet for 4 critically ill children in refractory status epilepticus, ranging in age from 9 weeks to 13.5 years after failure of traditional treatment. The ketogenic diet allowed these patients to be weaned off continuous infusions of anesthetics without r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
3
25
0
1
Order By: Relevance
“…Relatively low rates of adverse effects were noted, but these included gastrointestinal disturbances, electrolyte imbalance, and ketoacidosis, with the main causes of discontinuation being pancreatitis and hypertriglyceridemia [38,39]. These outcomes are consistent with those of other studies with fewer than 10 patients [41][42][43][44][45][46][47][48][49], and patients with FIRES have also been found to respond quickly after KDT initiation [40,46,47]. Most patients are good responders, weaning off infusion and successfully reaching ketosis, but the number of AEDs did not change significantly before and after undertaking a KDT [40,43].…”
Section: The Gut-brain Axis and Kdtssupporting
confidence: 82%
See 1 more Smart Citation
“…Relatively low rates of adverse effects were noted, but these included gastrointestinal disturbances, electrolyte imbalance, and ketoacidosis, with the main causes of discontinuation being pancreatitis and hypertriglyceridemia [38,39]. These outcomes are consistent with those of other studies with fewer than 10 patients [41][42][43][44][45][46][47][48][49], and patients with FIRES have also been found to respond quickly after KDT initiation [40,46,47]. Most patients are good responders, weaning off infusion and successfully reaching ketosis, but the number of AEDs did not change significantly before and after undertaking a KDT [40,43].…”
Section: The Gut-brain Axis and Kdtssupporting
confidence: 82%
“…Most patients are good responders, weaning off infusion and successfully reaching ketosis, but the number of AEDs did not change significantly before and after undertaking a KDT [40,43]. The age of patients has varied across studies, but even 6 to 10-week-old neonates with RE are reported to tolerate KDTs well [42,50]. Intravenous (IV) KDT is recommended for patients with underlying concomitant ileus [41,44,48], and early administration of IV KDT should be considered before switching to an enteral route [44].…”
Section: The Gut-brain Axis and Kdtsmentioning
confidence: 98%
“…Recent observations in patients with FIRES or other causes of RSE support the use, in the ICU, of less-conventional therapeutic options with suspected anti-inflammatory properties, such as the ketogenic diet (KD) or hypothermia [98][99][100]. Whether these mechanisms explain the favorable outcome of certain patients with FIRES remains to be demonstrated formally.…”
Section: Autoimmunity and Inflammation In Status Epilepticusmentioning
confidence: 95%
“…In patients with refractory LGS (2) Anoxic brain injury (2) epilepsy, KD is generally well tolerated with reported adverse effects such as gastrointestinal symptoms, metabolic acidosis, nephrolithiasis, and increased propensity to infections. 37 Five of the studies used in this review reported adverse effects from KD. 4,[15][16][17]34 The most common adverse effects reported in the reviewed studies were metabolic acidosis, hyperlipidemia, and hypoglycemia.…”
Section: Safety Of Kd In Adults With Sementioning
confidence: 99%